Impact of resilience building interventions in semiarid rural agro-communities: lessons from Mberengwa And Zvishavane Districts in South Eastern Zimbabwe - Musasa, Tatenda; Matsa, Mark Makomborero (Taylor & Francis, 2022)
The research sought to examine the impact of resilience building interventions toward rural livelihoods in Mberengwa and Zvishavane Districts. In this research, a mixed method research design was adopted to enhance the quality, complementarity, and expansion of results. Data were gathered using questionnaires, interviews and field observations. Questionnaires were distributed to 200 household heads in Mberengwa and 120 households selected in Zvishavane Districts using convenience sampling technique. Key informants interviewed included Lutheran Development Services representative, Rural District Council representative, District Crop and Livestock Officer (DCLO). The acquired qualitative data were subjected to content analysis while quantitative data was analyzed using SPSS version 23.0. The study findings show that Villages Savings and Lending, water harvesting, community horticultural gardens, apiculture, climate smart agriculture were some of the initiatives contributing to resilience building. These resilience building interventions contributed toward the attainment of Sustainable Development Goals 1; ending hunger, 2; zero hunger; and 13 climate action. The study recommends that the government, through the relevant ministry should ensure resilience building initiatives are included in their five-year plan, so that they have adequate and realistic implementation time frames.